Regulation of Flavonoid Biosynthetic Genes in Germinating Arabidopsis Seedlings. - Kubasek, WL (1992)
Many higher plants, including Arabidopsis, transiently display purple anthocyanin pigments just after seed germination. We observed that steady state levels of mRNAs encoded by four flavonoid biosynthetic genes, PAL1 (encoding phenylalanine ammonia-lyase 1), CHS (encoding chalcone synthase), CHI (encoding chalcone isomerase), and DFR (encoding dihydroflavonol reductase), were temporally regulated, peaking in 3-day-old seedlings grown in continuous white light. Except for the case of PAL1 mRNA, mRNA levels for these flavonoid genes were very low in seedlings grown in darkness. Light induction studies using seedlings grown in darkness showed that PAL1 mRNA began to accumulate before CHS and CHI mRNAs, which, in turn, began to accumulate before DFR mRNA. This order of induction is the same as the order of the biosynthetic steps in flavonoid biosynthesis. Our results suggest that the flavonoid biosynthetic pathway is coordinately regulated by a developmental timing mechanism during germination. Blue light and UVB light induction experiments using red light- and dark-grown seedlings showed that the flavonoid biosynthetic genes are induced most effectively by UVB light and that blue light induction is mediated by a specific blue light receptor.